Development of Open-Field Behaviour in the Medaka, Oryzias latipes - Lucon-Xiccato, Tyrone (Biology (Basel), 2020)
SIMPLE SUMMARY: Animal models play an important role in research on behaviour and its impairment. Fish larvae allow researchers to conduct experiments on large samples in just a few days and with small-scale experimental infrastructure, substantially increasing research output. However, several aspects of larval biology, including their behaviour, are frequently unknown. Our study has demonstrated that the most important behavioural paradigm for studying anxiety and stress in animals, the open-field test, can be used in the larvae of an important fish genetic model, the medaka. This finding will allow researchers to develop models to study anxiety and stress disorders based on medaka larvae. ABSTRACT: The use of juvenile and larval fish models has been growing in importance for several fields. Accordingly, the evaluation of behavioural tests that can be applied to larvae and juveniles is becoming increasingly important. We tested medaka at four different ages (1, 10, 30, and 120 dph) in the open field test, one of the most commonly used behavioural assays, to investigate its suitability for larvae and juveniles of this species. We also explored ontogenetic variation in behaviour during this test. On average, adult 120-day-old medaka showed higher locomotor activity in terms of distance moved compared with younger fish. Our analysis suggests that this effect was derived from both quantitative changes in locomotion related to the ontogenetic increase in fish size as well as qualitative changes in two aspects of locomotor behaviour. Specifically, time spent moving was similar between 1- and 10-day-old medaka, but progressively increased with development. In addition, we revealed that adult medaka showed constant levels of activity, whereas younger medaka progressively reduced their activity over the course of the entire experiment. The thigmotaxis behaviour typically used to assess anxiety in the open field test emerged at 120 days post-hatching, even though a difference in the temporal pattern of spatial preference emerged earlier, between 10 and 30 days post-hatching. In conclusion, some measures of the open field test such as total distance moved allow behavioural phenotyping in the medaka of all ages, although with some degree of quantitative and qualitative developmental variation. In contrast, immature medaka appear not to exhibit thigmotactic behaviour.